THE LEGAL INSTITUTION OF THE TRUST IN THE ECONOMY AND LAW OF EASTERN EUROPEAN COUNTRIES - Istvan Sandor (European Scientific Journal, ESJ, 2015)
The Anglo-Saxon trust is a legal institution that can be characterised by a rich variety of types and can serve a wide range of social and business needs. The popularity of the trust is attributable to its flexible structure, which allows asset partitioning, the function of the trustee and tracing. Without the adoption of English law in some form, the rules of civil law systems do not permit two different forms of ownership of the same thing at the same time. Strong economic demand, however, has forced several civil law countries to introduce a trust-like legal arrangement. The legal institutions drawn up in Russia, Georgia, Lithuania, Romania, the Czech Republic and Hungary, show varying degrees of similarity to the trust. The legal structures introduced include the contractual form, the right in rem, property without an owner and a contract with limited in rem effects. The rules of these legal vehicles differ from the trust in several ways. As a result, these institutions may fulfil the main functions of the trust to some extent, but they can approximate the trust only on a step-by-step basis to become real substitutes of the trust in the economy.